Myomectomy during cesarean section: is it a contraindication these days? - Gupta, Amit; Vij, Anju; Verma, Tanu; ., Molly; Kumar, Rajender; Gupta, Bharti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Myomectomy during the cesarean section is a debatable procedure because of raised risk of associated uncontrollable hemorrhage and postoperative morbidity. 38 years, elderly primigravida, who conceived after primary infertility with large leiomyoma in the lower uterine segment, underwent myomectomy during the cesarean section. Her intra-operative hemorrhage was within normal limits and post-partum period was uneventful. Conclusion of this study is Safety and feasibility of myomectomy along with cesarean largely depends upon the case selection, experience of the obstetrician and backup ICU and transfusion facilities.